The effect of structure on tensile properties of directionally solidified Zn-based alloys - Ares, Alicia Esther (2011)
The main objective of this study was to measure thermal (cooling rates, temperature gradients and velocities of the liquidus and solidus isotherms), structural (grain size and primary and secondary dendritic arm spacings) and tensile parameters (maximum tensile strength (MTS), yield strength (YS) and ultimate tensile strength (UTS)) in zincaluminum (ZA) hypoeutectic (Zn3 wt%Al) and hypereutectic (Zn10 wt%Al, Zn15 wt%Al, Zn20 wt%Al, Zn30 wt%Al, Zn37 wt%Al and Zn50 wt%Al) alloys directionally solidified, which present columnar, equiaxed and columnar-to-equiaxed transition (CET) structures. The different types of structures were analyzed with optical and Scanning Electron Microscopy (SEM). Correlations between temperature gradient, cooling rate, local solidification time, grain size and dendritic spacings and tensile tests parameters are presented and discussed. The results show the influence of concentration, microstructural arrangement and thermal conditions on the mechanical properties during the solidification process.